2015
DOI: 10.1016/j.sbspro.2014.12.533
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural Competence Training in Higher Engineering Education: The Role of Gaming Simulation

Abstract: The present study focuses on competency-based approach in higher engineering education. Today engineers are required to be socially, culturally and communicatively skilled and able to act in constantly changing sociocultural environment. Presently the development of engineers’ sociocultural competency is of great importance, which is seen from the criteria for accrediting engineering programs of numerous international organizations, e.g. ABET. The paper presents some methods of sociocultural competency trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…The use of computer tools for the simulation of engineering processes is presented as a more than interesting alternative to complement the theoretical foundations given in the classroom. It has been verified that the implementation of the simulation with didactic objects increase the interest of the students and their motivation [2].The teaching of thermodynamics approach has progressed from the traditional theoretical method with the use of computer technology allowing the student to have a greater participation in the development of classes [3], [4]. Ahmet Gurses [5], through the implementation of a t test found that the students instructed through interactive teaching performed significantly better than the traditional teaching method.…”
Section: Introductionmentioning
confidence: 95%
“…The use of computer tools for the simulation of engineering processes is presented as a more than interesting alternative to complement the theoretical foundations given in the classroom. It has been verified that the implementation of the simulation with didactic objects increase the interest of the students and their motivation [2].The teaching of thermodynamics approach has progressed from the traditional theoretical method with the use of computer technology allowing the student to have a greater participation in the development of classes [3], [4]. Ahmet Gurses [5], through the implementation of a t test found that the students instructed through interactive teaching performed significantly better than the traditional teaching method.…”
Section: Introductionmentioning
confidence: 95%
“…Using the computer games, literature [3][4][5][6][7] separately carried out teaching research on the object-oriented programming course, the industrial engineering introduction course, the university entrepreneurship education course, the business and market education course and the software engineering course. By educational computer games, the literature [8] studied computer education game evaluation, literature [9] studied the social and cultural force of higher education, the literature [10] studied the sustainable development of higher education.…”
Section: Overseas Research Statusmentioning
confidence: 99%
“…Professional competence of the engineer should be based upon his personal and professional culture, or rather be one of its components. To comprehend this category, we turn to modern understanding of the essence of an engineer (Galanina, 2015;Parkhomenko, 2008). The view of him as a narrowly focused specialist has proved its inconsistency.…”
Section: Introductionmentioning
confidence: 99%